2009
DOI: 10.1303/aez.2009.241
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Acorus calamus L. leaves and rhizome on mortality and reproduction of Callosobruchus chinensis L. (Coleoptera: Bruchidae)

Abstract: Laboratory and field experiments were conducted to investigate the bioefficacy of sweet flag (Acorus calamus) against the pulse beetle Callosobruchus chinensis, which infests stored chick pea seeds. Dried powders of the leaf and rhizome as well as their extracts in methanol (ME) and petroleum ether (PEE) were evaluated as bio-insecticides against the beetle. Rhizome powder (5 mg/g seed) was found to be more efficacious, causing 100% mortality, than leaf powder (20 mg/g seed), showing 91.1% mortality. Rhizome p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…All crude extracts evaluated via topical application against second instar S. litura larvae revealed that the ethanolic extract of P. retrofractum had the highest control efficiency, followed by A. calamus ( Table 2). P. retrofractum and A. calamus are used as alternative medicines and supplements in primary health care worldwide [29,30]. They are less toxic to nontarget organisms and mammals.…”
Section: Discussionmentioning
confidence: 99%
“…All crude extracts evaluated via topical application against second instar S. litura larvae revealed that the ethanolic extract of P. retrofractum had the highest control efficiency, followed by A. calamus ( Table 2). P. retrofractum and A. calamus are used as alternative medicines and supplements in primary health care worldwide [29,30]. They are less toxic to nontarget organisms and mammals.…”
Section: Discussionmentioning
confidence: 99%
“…β‐Asarone, a phenylpropanoid, is the primary constituent in the essential oil and crude extracts of Acorus calamus Linn (Sweet flag; Björnstad, Helander, Hultén, & Beck, ; Ganjewala & Srivastava, ; Raina, Srivastava, & Syamasunder, ). This plant is a well‐known ethnomedicinal and ethnobotanical plant worldwide (Shukla, Kumar, Prasad, Srivastava, & Dubey, ). Root and rhizome extracts of A. calamus contain many phytoconstituents, including—in addition to β‐asarone—alkaloids, caryophyllene, isoasarone, methyl isoeugenol, safrole, and acorin (Ganjewala & Srivastava, ; Wang, Cheng, & Fan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Leaf and rhizome powders of A. calamus and their extracts are significantly effective in feeding deterrence against the beetles Callosobruchus chinensis (Shukla et al, ) and Prostephanus truncates (Schmidt & Streloke, ). Essential oil of A. calamus is active against Helicoverpa armigera and Spodoptera litura (Tewary, Bhardwaj, & Shanker, ).…”
Section: Introductionmentioning
confidence: 99%
“…Natural antioxidants are generally classified as phenols, including flavonoids, phenolic acids and volatile compounds [ 7 ]. Acorus calamus is a traditional indigenous herb generally used in the treatment of cough, bronchitis, gout, tumours, haemorrhoids, skin diseases, numbness, and general debility [ 12 , 13 ]. It possesses a wide range of pharmacological activities, such as anti-diabetic [ 14 ], central nervous system depressant [ 15 ], anti-inflammatory [ 16 ], antioxidant [ 17 ], antispasmodic [ 18 ], antibacterial [ 19 ], antifungal [ 20 ], and cardiovascular [ 21 ] and insecticidal agent [ 22 ].…”
Section: Introductionmentioning
confidence: 99%